ANALISIS PENGARUH EVA, ROA, DAN ROE TERHADAP MVA PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ 45 DI BURSA EFEK INDONESIA (BEI) PERIODE 2011-2015 - Meuthia Rahmawati; Irni Yunita (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
This study aimed to examine the effect of Economic Value Added (EVA), Return on Asset (ROA), and Return on Equity (ROE) to Market Value Added (MVA)on listed LQ 45 company in Indonesia Stock Exchange Period 2011-2015. This methodology research using panel data regression. Population in this research are listed LQ 45 company in Indonesia Stock Exchange Period 2011-2015. Sampling technique that used in this research is purposive sampling and resulting 22 companies as the samples. This study used the annual reports companies that listed in Indonesia Stock Exchange periode 2011-2015. The result shows that Economic Value (EVA) and Return on Asset (ROA) partially has no significant effect on Market Value Added (MVA), while Return on Equity (ROE) partially has significant effect on Market Value Added (MVA).. Economic Value Added (EVA), Return on Asset (ROA), and Return on Equity (ROE) has simultaneous effect on Market Value Added (MVA).